ALLIUM STENT IN EXTENSIVE URETERAL STENOSIS: LESSON LEARNED FROM ITS FIRST OFF LABEL USED IN INDONESIA - Nainggolan, Ebram; Hudaya, Syamsu; Wallad, Caesar Khairul; Firdianto; Rahman, Fakhri (Indonesian Urological Association, 2024)
Objective: This study aims to determine the use of allium stents for ureteral stenosis. Case(s) Presentation: This study reported a case of 50-year-old-male with right ureteral stenosis that underwent allium installation, the first ever used in Indonesia. Discussion: . Long-term ureteral stenting is commonly used when major surgery is not an option for patients. Metallic stents offer an alternative method to address the blockage in a single procedure, without the risk of issues like tissue erosion, infection, or tube encrustation. The design of the Allium stent ensures that the ureter remains open by providing direct support to the walls, resulting in better dilation compared to the double-J stent. In this study, the patient who received an Allium stent could benefit from its use. The stent has shown effectiveness in treating ureteral stenosis, relieving bothersome urinary symptoms, and reducing the need for frequent visits to the operating room for JJ stent replacement. Conclusion: Allium stents improve quality of life in patients with irritative symptoms from JJ stents, reducing Re-operations of JJ insertion, and hospital stay. Keywords: Ureteral stenosis, allium stent, Indonesia.